PENGARUH INDUKSI MEDAN MAGNET EXTREMLY LOW FREQUENCY (ELF) TERHADAP PERTUMBUHAN PIN HEAT JAMUR KUPING (Auricularia auricula) - Mardika Wulansari; Rif'ati Dina Handayani; Sudarti sudarti (FKIP Universitas Jember, 2017)
In this modern era, the utilization of Extremely Low Frequency (ELF) magnetic field on variety of technology is increased. This increase occurs in variety of technology like food, health, industry, communications and agriculture. One of the food that can be cultivated through the agricultural sector is ear mushroom (Auricularia auricular). This studies are aims to investigate the influence of magnetic field on ear mushroom with intensities, 100 μT, 300 μT, and 600 μT with long exposure of 10 minutes, 30 minutes, 50 minutes, and 70 minutes and determining the effective dose for the growth of heat pin mushroom. This study was using completely randomized design with one primary factor and three replications. The result showed that the magnetic field produces results fairly significant increase in heat pin mushroom growth. Result in each of the experimental class increased by the rise of magnetic field intensities with lowest growth of heat pin getting by 600 μT for 70 minute, and the day of coming up heat pin on 22,33 Hsi and highest growth of heat pin getting by control class with the day of coming up heat pin on 24,44 Hsi. Key word : Ekstremly Low Frequency (ELF), Ear Mushroom, Heat Pin